An aggregated non-destructive testing (NDT) framework for the assessment of mechanical properties of unreinforced masonry Italian medieval churches. (1st August 2022) - Pirchio, David; Walsh, Kevin Q.; Kerr, Elizabeth; Giongo, Ivan; Giaretton, Marta; Weldon, Brad D.; Ciocci, Luca; Sorrentino, Luigi
Highlights: Extensive material classification of unreinforced masonry Italian medieval churches (72 churches included in the research). Extensive in-situ testing of historic unreinforced masonry using non-destructive testing techniques and expert judgment-based techniques (170 specimen included in the research). Development of predictive equations to determine compressive strength, Young's modulus, and shear modulus of historic unreinforced masonry via SonReb procedure. Partial validation of the developed equations via destructive testing of specimens coming from relatively modern unreinforced masonry. Abstract: Medieval churches constructed of unreinforced masonry (URM) represent critical assets of Italian architectural heritage. In order to preserve these churches against earthquakes, obtaining robust information regarding their material mechanical characteristics is necessary as part of a reliable structural analysis and strengthening intervention program. Given the drawbacks of semi-destructive or destructive testing of heritage material, non-destructive testing (NDT) is the most viable approach to obtain data regarding the mechanical characteristics of the material composing the structure of the churches. However, there are several uncertainties inherent within NDT techniques based on the current state of the art. Thus, two different NDT techniques (i.e., rebound hammer testing, and pulse velocity testing) and two expert judgment-based investigation techniques (i.e., masonry quality index, and mechanical properties ranges based on the Commentary to the Italian building code) were applied to 170 specimens belonging to the walls of 72 URM Italian medieval churches to assess the quality of the URM and its components. The surveyed churches walls, although highly variable in geometry, materials, and conditions, can be classified into four URM types: a) irregular stone masonry with pebbles, erratic and irregular stone units; b) roughly cut stone with good bond; c) ashlar masonry with regular squared blocks and mortar joints; and d) solid fired clay bricks with lime mortar. Subsequently, using the SonReb technique, predictive equations that aggregate the two NDT techniques and the correlation coefficient specific for each URM type were developed to define some of the critical mechanical properties of the URM (i.e., compressive strength, Young's modulus, and shear modulus). The mechanical properties determined via predictive equations were then plotted and compared with the predictions of the two well-established expert judgment-based investigation techniques to evaluate the accuracy of the approach. Finally, a partial validation based on NDT and destructive testing techniques of six URM prisms was performed to evaluate the accuracy of the proposed predictive equations. Ultimately, three equations to determine the compressive strength, the Young's modulus, and the shear modulus were developed. The developed equations offer to engineering practitioners a rapid NDT technique to assess URM properties that do not solely rely on the judgment and expertise of the practitioner.